Longitudinal analysis of raccoon rabies in West Virginia, 2000–2015: a preliminary investigation - Plants,K. Bert; Wen,Sijin; Wimsatt,Jeffrey; Knox,Sarah (PeerJ, 2018)
Animal borne rabies virus is a source of infection in humans, and raccoons (Procyon lotor) are the primary terrestrial reservoir in West Virginia (WV). To assess the behavior and status of raccoon variant rabies virus (RRV) cases in WV, a longitudinal analysis for the period 2000–2015 was performed, using data provided by the state Bureau of Public Health. The analytic approach used was negative binomial regression, with exclusion of those counties that had not experienced RRV cases in the study period, and with further examination of those counties where oral rabies vaccine (ORV) baits had been distributed as compared with non-ORV counties. These analyses indicated that there had been a reduction in numbers of RRV positive animals over the study period, predominantly due to a decrease in raccoon infections. Non-raccoon hosts did not appear to have a similar decline, however. The rates of decline for the ORV zone were found to be significantly greater as compared to the non-ORV area. The study was limited by the lack of data for season or point location of animal collection, and by lack of surveillance effort data. Even so, this study has implications for the preventive measures currently being implemented, including expanded vaccination effort in domestic animals. Spatial analyses of RRV and further examination of the virus in non-raccoon hosts are warranted.
Keywords: West Virginia; Longitudinal analysis; Rabies; Infectious disease